Economic valuation of cactus pear production in semi-arid regions of Mexico - Louhaichi, Mounir; Hassan, Sawsan; Yigezu, Yigezu; Mata-Gonzalez, Ricardo (2022)
Dataset about cactus pear production and economic evaluation in Mexico. The dataset is part of a survey series, targeting farmer planting cactus across 5 countries: Tunisia, India, Jordan, Mexico and Chile.